2022
DOI: 10.1038/s41467-022-28677-y
|View full text |Cite
|
Sign up to set email alerts
|

Kastor and Polluks polypeptides encoded by a single gene locus cooperatively regulate VDAC and spermatogenesis

Abstract: Although several long noncoding RNAs (lncRNAs) have recently been shown to encode small polypeptides, those in testis remain largely uncharacterized. Here we identify two sperm-specific polypeptides, Kastor and Polluks, encoded by a single mouse locus (Gm9999) previously annotated as encoding a lncRNA. Both Kastor and Polluks are inserted in the outer mitochondrial membrane and directly interact with voltage-dependent anion channel (VDAC), despite their different amino acid sequences. Male VDAC3-deficient mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…Mice without both Kastor and Polluks expression exhibit severely impaired male fertility due to abnormal mitochondrial sheath formation. These authors conclude that cooperative function of these polypeptides in the regulation of VDAC3 may be essential for mitochondrial sheath formation in spermatozoa (72). Moreover, the relationship between lncRNA and spermatogenesis in association with the extracellular matrix and spermatogenesis (73) and in varicoceleinduced spermatogenic dysfunction has also been demonstrated (74).…”
Section: Recent Finding On Mirna/lncrna Processingmentioning
confidence: 86%
“…Mice without both Kastor and Polluks expression exhibit severely impaired male fertility due to abnormal mitochondrial sheath formation. These authors conclude that cooperative function of these polypeptides in the regulation of VDAC3 may be essential for mitochondrial sheath formation in spermatozoa (72). Moreover, the relationship between lncRNA and spermatogenesis in association with the extracellular matrix and spermatogenesis (73) and in varicoceleinduced spermatogenic dysfunction has also been demonstrated (74).…”
Section: Recent Finding On Mirna/lncrna Processingmentioning
confidence: 86%
“…The ultrastructure and formation of the mitochondrial sheath have been described in previous studies, and knockout of several genes ( e.g. , ARMC12 [ 3 ], SPATA33 [ 24 ], and VDAC3 [ 25 , 26 ]) is known to cause abnormal mitochondrial sheath formation and subsequent infertility [ 27 ]. These studies have also shown that the integrated formation of the mitochondrial sheath is closely related to sperm motility [ 3 , 25 ], thus these observations of morphological and structural abnormalities in the mitochondrial sheaths of Morn2 –/– spermatozoa are likely to contribute to the observed sperm motility defects and male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide translation profiling has recently revealed that small ORFs identified in lncRNA genes can code for micropeptides, polypeptides with a length of less than 100 amino acids essential for cellular growth (Chen et al, 2020). Other small peptides produced from lncRNAs have also been reported in functional studies (Odermatt et al, 1997;MacLennan and Kranias 2003;Slavoff et al, 2013;Ruiz-Orera et al, 2014;Pang, Mao, and Liu 2018;Hartford Corrine and Lal, 2020;Nita et al, 2021;Mise et al, 2022). Eukaryotic lncRNA genes are usually composed of multiple exons with an average of 2.49 exons per human lncRNA gene (Khan, Wellinger, and Laurent 2021).…”
Section: Contribution Of Long Non-coding Rnas and Circular Rnasmentioning
confidence: 99%